+0  
 
0
150
1
avatar

(25-a) (2a+3)= 40

Guest Feb 23, 2017
 #1
avatar+12561 
+5

(25-a) (2a+3)= 40     Multiply it out

50a + 75 - 2a^2-3a = 40     and collect 'like' terms

-2a^2 +47a +35 = 0    use quadratic formula\(x = {-b \pm \sqrt{b^2-4ac} \over 2a}\)

 

-47+-sqrt(2209+280)    /   -4     =     - 47+-49.8898    /-4   =  24.222   or  -.7225

ElectricPavlov  Feb 23, 2017

7 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.